Antibiotherapy at birth in very low birth weight infants before and after the use of interleukin 6 as an infectious biomarker in a tertiary level unit - Sonia Lareu-Vidal; Gonzalo Solís-Sánchez; María Caunedo-Jiménez; Silvia Martín-Ramos; Marta Costa-Romero; Belén Fernández Colomer (Permanyer, 2021)
Background: Neonatal sepsis is a condition with high mortality and morbidity that contributes to high rates of antibiotic therapy at birth. In addition, very low birth weight newborns (VLBWN) are particularly vulnerable. Interleukin 6 (IL-6) seems to be an early and effective marker that could help a better selection of patients to be treated. This study aimed to evaluate the use of antibiotics in the first 72 hours of life in VLBW infants before and after using IL-6 as an infection marker. Also, we wanted to analyze the differences in morbidity and mortality during admission and other factors associated with the decision to start antibiotic treatment. Methods: We conducted a cohort retrospective study. We included VLBWN born in our hospital or admitted before 72 hours of life in two two-year periods (2007-2008 and 2011-2012). Results: Antibiotics use during the first 72 hours of life was analyzed as the primary variable, which was reduced by 20% on the second period (p = 0.002). Regarding the analysis of secondary variables, we found no significant differences in mortality during hospital admission and the incidence of nosocomial sepsis, enterocolitis, or invasive fungal infection. The multivariate analysis indicated extreme prematurity and the study group as the most strongly related factors to the start of antibiotic therapy. Conclusions: IL-6 was a useful marker of infection to reduce the use of antibiotic therapy in VLBW infants without increasing mortality.